Blood pressure trends following birth in infants born under 25 weeks' gestational age: a retrospective cohort study - Alexander Rakow; Emma Persad; Björn Brindefalk (BMJ Publishing Group, 2024)
Objective The aim of our study was to describe postnatal blood pressure (BP) trends and evaluate relevant dynamics and outcomes for a subgroup of extremely preterm (EPT) infants.Design Retrospective observational cohort study.Setting Patients admitted to Karolinska University Hospital Stockholm.Patients EPT infants born between 22+0 and 24+6 weeks' gestational age (GA) undergoing invasive, continuous BP monitoring through an umbilical arterial catheter.Main outcome measures Physiological BP trends, the influence of cardiovascular active interventions and fluid boluses on BP, and relevant adverse outcomes, including intraventricular haemorrhage (IVH), necrotising enterocolitis (NEC) and death, were mapped over the first week of life.Results We included 125 infants between January 2009 and November 2021. Mean BP values were 31 mm Hg, 32 mm Hg and 35 mm Hg, at 3 hours, 24 hours and 48 hours, respectively. A pronounced BP dip and nadir were observed around 20 hours, with a mean BP value of 32 mm Hg. 84% received fluid boluses within the first week of life; however, we could not observe any noteworthy change in BP following administration. Only 8% of patients received cardiovascular active drugs, which were too few to infer drug-specific effects. Overall, 48% developed IVH, 15% developed NEC and 25% died.Conclusions Approximating clinically acceptable mean BP values using GA gives underestimations in these infants. The postnatal BP dip should be regarded as a physiological phenomenon and not automatic grounds for interventions which may momentarily stabilise BP but have no appreciable short-term or long-term effects. Further studies are warranted for improved understanding of clinically relevant trends and outcomes.